1996
DOI: 10.1038/sc.1996.81
|View full text |Cite
|
Sign up to set email alerts
|

Cost of traumatic spinal cord injury in a population-based registry

Abstract: This prospective study examines a population based cohort of 115 Coloradans identified as having an acute traumatic spinal cord injury by the Spinal Cord Injury Early Notification System in 1989. Comprehensive medical cost and complication data were collected for the first 2 years of survival. Unlike previous cost studies, this group represents the broad spectrum of spinal cord injured persons, reflected in a truly population based sample. Nearly 22 million dollars were spent during the first 2 years post inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 6 publications
2
72
0
Order By: Relevance
“…Specialized CBT o ered in the rehabilitation phase resulted in almost 15% less re-admissions than those who receive standard rehabilitation services. Research 16 has shown the cost of SCI during the 2 years after the injury to be $22 million in 1992 US dollars value. Much of this cost was due to physical complications and re-admissions.…”
Section: Discussionmentioning
confidence: 99%
“…Specialized CBT o ered in the rehabilitation phase resulted in almost 15% less re-admissions than those who receive standard rehabilitation services. Research 16 has shown the cost of SCI during the 2 years after the injury to be $22 million in 1992 US dollars value. Much of this cost was due to physical complications and re-admissions.…”
Section: Discussionmentioning
confidence: 99%
“…1,7 High Tetraplegia cases received a higher mean first-year payment for DME ($81,241) than was reported by De Vivo et al 1 and Johnson et al 7 whose reported mean DME costs were $30,356 and $45,970, respectively. Current Low Tetraplegia cases received higher average payments for DME ($70,463) in comparison to the means reported by De Vivo et al and Johnson et al, which were $24,450 and $19,547, respectively.…”
Section: Durable Medical Equipmentmentioning
confidence: 77%
“…7,12 As several of the studies [8][9][10][11] reported LOS and payments for all levels of SCI combined, it is difficult to make comparisons with the current findings. These duration differences may be explained by a study by Fiedler et al, 9 who found that significant decreases in LOS occurred over time from 1972 to 1997 for both acute hospitalization and rehabilitation.…”
Section: Acute Hospitalization and Rehabilitationmentioning
confidence: 83%
See 2 more Smart Citations